2018
DOI: 10.1080/07380577.2018.1497820
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting social participation of Iranian children with cerebral palsy

Abstract: The purpose of this study was to identify the factors affecting the social participation of Iranian children with cerebral palsy (CP). Participants were 274 (male = 62%; female = 38%) children with CP, 6- to 12-years old (mean = 1.64) and their parents. Several standardized measures were used to assess social participation, gather environmental factors, and demographic questionnaires. The results of stepwise linear regression analysis indicated that the type of CP, Manual ability level and cognitive level (IQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The literature search yielded 9511 unique articles. In total, 34 articles met all inclusion criteria [5,9,[17][18][19][20][21][22][23][24][25][26], of which 20 described participation attendance and/or involvement [19][20][21][22][23][24][25][26][37][38][39][40][41][42][43][44][45][46][47][48], and 14 described one or more participation-related constructs [5,9,15,17,18,[49][50][51][52][53][54][55][56][57]. Cross-reference checking did not result in any additional articles (see Figure 1 for a flowchart of the article selection).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature search yielded 9511 unique articles. In total, 34 articles met all inclusion criteria [5,9,[17][18][19][20][21][22][23][24][25][26], of which 20 described participation attendance and/or involvement [19][20][21][22][23][24][25][26][37][38][39][40][41][42][43][44][45][46][47][48], and 14 described one or more participation-related constructs [5,9,15,17,18,[49][50][51][52][53][54][55][56][57]. Cross-reference checking did not result in any additional articles (see Figure 1 for a flowchart of the article selection).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding participation, 20 studies reported on participation attendance [19][20][21][22][23][24][25][26][37][38][39][40][41][42][43][44][45][46][47][48], of which 4 studies also reported on participation involvement [21,40,41,47]. Table 3 and Supplementary Appendix 2 show all environmental factors assessed and associated with participation attendance or involvement in these studies.…”
Section: Participation Attendance and Involvementmentioning
confidence: 98%
See 2 more Smart Citations
“…Occupational performance is also the focal point of occupational therapy models. Therefore, evaluation of occupational performance, functional ability, and social participation should be the top priority in occupational therapy assessments (Amini, Saneii, & Pashmdarfard, 2018; Mathiowetz, 1993; Steultjens et al, 2004). At present, occupational therapists use models (such as ICF) that define participation as a combination of several factors (including environmental, personal, and physical factors).…”
Section: Discussionmentioning
confidence: 99%